2015
DOI: 10.1016/j.sbspro.2014.12.614
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Child's Attachment with Proximity Relationships in Family

Abstract: Attachment is valuable for a child for purposes of security and self-preservation, his future behavior and socialization. Our research, conducted in the framework of inter-generational transmission of individual's relations system, investigates the corelation between indicators of attachment and affection of mothers and grandmothers and child's attachment to his mother. The study involved 30 triads (child -mother -grandmother). The results revealed that mothers' and grandmothers' confidence in significant pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…Children with insecure attachment rarely share secrets and difficulties with their mothers. The obtained results confirm the famous data of the peculiarities of children with insecure attachment[7].Thus, these children show no signs of striving for the emotional proximity to their mother; they feel her uncertainty, non-acceptance and lack of support. Note that chil-dren with both secure and insecure attachment need their mothers to present.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Children with insecure attachment rarely share secrets and difficulties with their mothers. The obtained results confirm the famous data of the peculiarities of children with insecure attachment[7].Thus, these children show no signs of striving for the emotional proximity to their mother; they feel her uncertainty, non-acceptance and lack of support. Note that chil-dren with both secure and insecure attachment need their mothers to present.…”
supporting
confidence: 85%
“…This influence was found in some clinical studies [1]. The early study under the author's supervision has revealed that the demonstration of assurance in the secure relations of proximity by adults (mother, grandmother) who educate a child enable to develop child's dominance related to the need for trust and empathy in behavior [7]. Therefore, the data analysis has shown that the quality of attachment to mother affects the psychological health of senior pre-school children.…”
Section: Discussionmentioning
confidence: 89%